Analysis of Work Accidents in Shipyards Using FMEA and FTA Methods with a Systematic Literature Review Approach - Sigit, Nanta; Wirawan Aryanto Balol; Bayu Firmanto (International Journal of Technology and Education Research, 2026)
Occupational accidents in shipyard industries remain a significant concern due to the complex and high-risk nature of shipbuilding and repair activities. Operations such as working at heights, confined space entry, welding, heavy lifting, and exposure to hazardous substances contribute to elevated accident rates and severe consequences, including fatalities and economic losses. This study aims to analyze occupational accidents in shipyards by integrating Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) using a Systematic Literature Review (SLR) approach. The objective is to identify dominant accident types, prioritize critical risks, and determine root causes to support evidence-based safety improvements. The research employed a systematic literature review method by collecting peer-reviewed articles from major scientific databases published between 2010 and 2024. Relevant studies were selected based on predefined inclusion and exclusion criteria. Data were extracted and synthesized to identify common failure modes, risk parameters (Severity, Occurrence, Detection), Risk Priority Number (RPN) values, and causal relationships derived from FTA models. The PRISMA framework was applied to ensure a transparent and structured selection process. The results indicate that the most dominant occupational accidents in shipyards include falls from height, confined space incidents, fire and explosions during hot work, crushing injuries from heavy lifting operations, and electrical accidents. FMEA analysis revealed that confined space operations and welding activities consistently present the highest RPN values. FTA findings demonstrate that these accidents are commonly caused by a combination of human factors, equipment failures, inadequate supervision, insufficient safety procedures, and weak organizational safety culture. The integration of FMEA and FTA provides a comprehensive analytical framework that combines quantitative risk prioritization with qualitative root cause identification. This integrated approach enhances the effectiveness of occupational risk assessment in shipyard environments. Academically, the study contributes to the development of integrated risk analysis methodologies, while practically it offers structured recommendations for improving safety management systems in shipyard industries.